UPAYA KONVERGENSI TELEVISI LOKAL MELALUI PROGRAM BERITA BERBAHASA LOKAL ( Kajian Terhadap Program Berita JTV : Pojok Kampung, Pojok Medhureh, dan Pojok Kulonan menggunakanCommunication Accomodation Theory-CAT ) - Andiwi Meifilina (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2016)
The phenomenon of the existence of the mass media through which the local television program for viewers to give plenty of options in accordance with the language and culture of each as well as a means of communication to understand the language of different cultures within a single province. JTV stands for Java Pos Television merpakan largest local television station in East Java Province and is the first local television in Indonesia which was established as a locally based broadcasters with the cultures of East Java are highly diverse. There are several languages used as languages of East Java community Suroboyoan wetanan inherent in citizens of Surabaya, Sidoarjo, Malang and Mojokerto. Further languages are attached to the Madurese community Pasuruan, Probolinggo, Jember and Lumajang and Mataraman Java language that is identical to the citizens of East Java Kulonan Blitar, Tulungagung, Kediri and Madiun.JTV accommodate the different variety of language through news programs' Corner Village (Suroboyoan language), corner Medhureh (Madura language), corner Kulonan (Javanese Kromo).